Novel CHATogether family-centered mental health care in the post-pandemic era: a pilot case and evaluation - Caylan J. Bookman; Julio C. Nunes; Nealie T. Ngo; Naomi Kunstler Twickler; Tammy S. Smith; Ruby Lekwauwa; Eunice Y. Yuen (BMC, 2024)
Abstract Background The COVID-19 pandemic impacted children, adolescents, and their families, with significant psychosocial consequences. The prevalence of anxiety, depression, and self-injurious behaviors increased in our youth, as well as the number of suicide attempts and hospitalizations related to suicidal ideation. Additionally, parents' mental health saw increasing rates of depression, irritability, and alcohol use combined with worsening family function, child-parent connectedness, positive family expressiveness, and increases in family conflict. In light of these statistics, we created CHATogether (Compassionate Home, Action Together), a pilot family-centered intervention using multi-faceted psychotherapeutic approaches to improve familial communication and relational health between adolescents and their parents. This paper discusses the implementation of the CHATogether intervention at the Adolescent Intensive Outpatient Program (IOP), providing an example of the intervention through an in-depth pilot case, and evaluation of the program's acceptability and feasibility. Methods This paper describes a case in detail and evaluation from a total of 30 families that completed CHATogether in the initial pilot. Each family had 4-6 one-hour CHATogether sessions during their 6-week treatment course at the IOP. Before and after CHATogether, adolescents and their parents separately completed a questionnaire designed to explore their perceived family conflicts. After completion of the program, participants completed a brief quality improvement survey to assess their overall experience with CHATogether. In the reported case, the family completed Patient-Reported Outcomes Measurement Information System (PROMIS) depressive and anxiety symptoms scales, Conflict Behavior Questionnaires (CBQ), 9-item Concise Health Risk Tracking Self-Report (CHRT-SR9), and help-seeking attitude from adults during distress and suicide concerns. Results The pilot case showed a trend of improvement in reported depressive and anxiety symptoms, child-parent conflicts, subfactors of suicide risk including pessimism, helplessness, and despair, help-seeking acceptability from parents for suicide concerns, and the establishment of individualized family relationship goals. Preliminary feedback from participating families demonstrated positive effects on intra-family communication and improvement in the overall family dynamic. Adolescents (n = 30/30) and their parents (n = 30/30) rated "strongly agree" or "agree" that their families had benefited from CHATogether and welcomed participation in future program development. Conclusion This study presents CHATogether as a novel family-centered intervention to address post-pandemic family mental health stress, especially when a family system was disrupted and negatively affected the mental health of children and adolescents. The intervention facilitated positive child-parent communication on a variety of topics, through tools such as emotional expression and help-seeking behavior. The reported pilot case and evaluation suggested CHATogether's acceptability and feasibility in a clinical context. We also provided quality improvement feedback to guide future studies in establishing the efficacy of CHATogether and other similar models of clinical family interventions.